Mediating role of self-efficacy on the relationship between loneliness and depression among community-dwelling older persons at Na Khayat subdistrict, Thailand - Suwanmanee, Suttama; Minhat, Halimatus Sakdiah; Ying, Lim Poh; Ismail, Adibah Hanim (Universiti Putra Malaysia Press, 2024)
Introduction: The ageing population has brought along various health implications, with an increasing prevalence of depression among older persons, particularly those experiencing loneliness. This study aimed to determine the mediating role of self-efficacy on the relationship between loneliness and depression among older persons. Methods: A total of 450 older persons aged 60 and older were randomly recruited from Health Promoting Hospitals in the three zones under the Na Khayat Subdistrict. Confirmatory factor analysis (CFA) was conducted to verify the factor structure of the observed variables, with the interrelationship between variables studied using structural equation modelling (SEM). A mediation analysis was completed via Bootstrap Analysis. Results: From the study, at least one in every 10 participants (10.4%) experienced depressive symptoms. Three-quarters (75.1%) of them had low levels of loneliness while 10.4% had depressive symptoms with loneliness. The CFA results showed acceptable indices of the structural model (χ2 =1133.414, df =342, Relative χ2 = 3.314, GFI = 0.833, AGFI = 0.801, CFI = 0.807, RMSEA = 0.072). The path analysis showed that seven variables had significant causal relationships with depression (R2 = 0.441, p < 0.05), including employment, source of household income, living arrangement, social support, perception of health, self-efficacy, and loneliness. The mediation regression analysis showed a partial mediation effect of self-efficacy on the relationship between loneliness and depression. Conclusions: Self-efficacy plays a major role in preventing the development of depression among older persons with loneliness. Self-efficacy interventions should be integrated into various programmes to prevent depressive symptoms. Malaysian Journal of Medicine and Health Sciences (2024) 20(3): 133-141. doi:10.47836/mjmhs.20.3.19 © 2024 Universiti Putra Malaysia Press. All rights reserved.